2012
DOI: 10.6061/clinics/2012(09)19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lung preservation solutions in human lungs using an ex vivo lung perfusion experimental model

Abstract: OBJECTIVE:Experimental studies on lung preservation have always been performed using animal models. We present ex vivo lung perfusion as a new model for the study of lung preservation. Using human lungs instead of animal models may bring the results of experimental studies closer to what could be expected in clinical practice.METHOD:Brain-dead donors whose lungs had been declined by transplantation teams were used. The cases were randomized into two groups. In Group 1, Perfadex® was used for pulmonary preserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The degree of pulmonary edema is inversely proportional to the quality of lung preservation [19]. Several experimental models have used edema measurement to evaluate the efficacy of protective drugs against IRI after LTx [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of pulmonary edema is inversely proportional to the quality of lung preservation [19]. Several experimental models have used edema measurement to evaluate the efficacy of protective drugs against IRI after LTx [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A small number of groups investigated isolated, ex vivo perfused, and ventilated human lungs or lobes . In these models, lung tissue was perfused via the cannulated pulmonary artery with cell free perfusion media, with cell‐containing (e.g., diluted whole human blood preparations) solutions, or solutions for lung preservation during transport before transplantation .…”
Section: Existing Co‐cultures and 3d Models For Pulmonary Researchmentioning
confidence: 99%
“…A small number of groups investigated isolated, ex vivo perfused, and ventilated human lungs or lobes . In these models, lung tissue was perfused via the cannulated pulmonary artery with cell free perfusion media, with cell‐containing (e.g., diluted whole human blood preparations) solutions, or solutions for lung preservation during transport before transplantation . The lungs were ventilated via the natural airways for up to 24 h. Such limited available and technically elaborated models allow for the investigation of lung edema formation, oxygenation capacity, vascular reactivity, bacterial infection, and innovative therapeutic approaches such as stem cell therapies .…”
Section: Existing Co‐cultures and 3d Models For Pulmonary Researchmentioning
confidence: 99%
“…(30) The preservation method is pulmonary artery perfusion with a preservation solution at 4°C, which may cool the tissue evenly and remove blood from the pulmonary vascular bed, preventing thrombosis and attenuating cellular injury caused by macrophages and neutrophils. (31) In a rat model of double lung transplantation, a comparative study of lung preservation solutions revealed low potassium dextran provided superior graft function to Euro-Collins, low potassium Euro-Collins and University of Wisconsin solution after extended ischemia. (32) In a porcine lung transplantation model, after 24 hours of cold ischemia, low potassium dextran or Celsior solution provided safe pulmonary preservation, while surfactant activity was affected to the same extent.…”
Section: Preventionmentioning
confidence: 99%